Analysis of key indicators that affect the expected benefit of customers when using loyalty cards - Jelena Končar; Radenko Marić; Goran Vukmirović (Journal of Business Economics and Management (JBEM), 2019)
The aim of this paper is to define the significance of different indicators that affect the expected benefit of customers when using loyalty cards in the purchasing process in the retail sector. As the most important indicators that affect expectations while using loyalty cards, the following was tested: price discounts, more efficient service and rewards, personalized communication, payment option, better information, status symbols and additional benefits. The research was conducted on a sample of 552 holders of loyalty cards of the largest retail chains in selected Central Europe (CE) and South East Europe (SEE) countries. The values of indicators for different categories of customers and different markets can be determined based on the obtained results and conducted tests. The determined values of the indicators are the basis for the formation of a regression model that will serve the chain managers to optimize the loyalty programs in relation to the identified customer expectations.
Keywords: L81; L84; M31; 650; loyalty cards; retailing; retail sector; customers; customers' loyalty; customers' benefits; loyalty programs; CE and SEE countries